Peak your profits - Blackman, Jeff (Advantage Quest Pub, 1996)
Outsell. Outserve. Outmarket. Outnegotiate Your Competition! After 15-plus years of testing, research and development, Jeff reveals his explosive business-growth system. Peak Your Profits is unique, because it's the first book to collectively focus on the core business-growth skills: sales, marketing, client development, relationship building, service and negotiations. It's your blueprint for peak profits! (Selected by Fast Track as one of "the best business books on tape.")